Effect of Wind Shear Coefficient for the Vertical Extrapolation of Wind Speed Data and its Impact on the Viability of Wind Energy Project - Saif ur Rehman; Muhammad Shoaib; Imran Siddiqui; Firoz Ahmed; Muhammad Rashid Tanveer; Saif Uddin Jilani (Journal of Basic & Applied Sciences, 2015)
The importance of characterizing the wind shear at a specified location for the utilization of wind turbine is of vital importance. Such study is considered necessary both for the turbine design and prediction of its power output. In situations where the wind speed at different heights is required if measured values are known at one height then, generally it is extrapolated to the hub height by using the one-seventh power law. The exponent in this case has a value of 1/7 but it is observed that, the value of exponent varies with the type of terrain therefore; the one-seventh power law is not suitable for wind speed extrapolation and energy estimation. It has been found that, the one-seventh power law has a tendency to miscalculate the actual long-term average wind speeds. Hence, for accurate estimation of wind speed at a height, both monthly or seasonal and diurnal values of wind shear coefficient (WSC) have to be used. In this paper, the power law exponent for three sites located over coastal sites in South of Pakistan, i.e., Katibandar, Jati and Gharo, is established using wind speeds measured at heights 10 m and 30 m above the ground (AGL). Wind data is obtained from Pakistan Meteorological | department (PMD). Mean values of WSC were found to be 0.318 at Jati, 0.321 at Gharo and 0.269 at KatiBander. In addition, yearly, monthly and diurnal variation for WSC is also analyzed. The research showed that, the wind shear coefficient significantly fluctuates by seasonal and diurnal changes. Comparisons has been made for discrepancies in energy estimation, payback period and cost of energy (Cents/Kwh) using wind speed values extrapolated from 10 m, for one-seventh power law and overall mean WSC as exponent. The study showed that, if wind speed is extrapolated with WSC of 0.143, the energy is underestimated by 16-33% at Gharo, 12-25% at Katibandar and 28-51% at Jati for all considered hub heights. Error in the Payback period is estimation as 19–34% at Gharo, 16–27% at Katibandar and 31–48% at Jati for all considered hub heights, for 10 m wind data extrapolated with WSC of 0.143. The percentage change in the COE estimation for the two wind shear factors and three sites under study show that, if 10 m wind data extrapolated with WSC 0.143, the COE overestimated is between 19-34% for Gharo, 16-27% for Katibandar and 31- 48% for Jati for all considered hub heights. It is evident from results that, the 1/7 power law, tends to produce misleading results for the feasibility study.